Informing Policymakers About the Impact of State Funding Formula Components on Rural Schools - Gerald R. Bass; Deborah Verstegen (Journal of Research in Rural Education, 1991)
This paper is focused on both the conceptual framework for the financial treatment of small schools and/ or school districts and the actual status of such schools within existing state finance systems. The first segment provides a brief review of research on the association between school size and educational outcomes. The policy implications ofthat research are then considered. The thirdportion of the paperis devoted to adescription of current state finance formulas, which are reviewed with a particular emphasis on sparsity and geographical isolation factors. Finally, some policy considerations relative to the use of such factors are identified.